Water birds from Agua Dulce lake and El Ermitaño estuary, Jalisco, Mexico. - Hernández-Vázquez, Salvador (2005)
Waterbird abundance, and seasonal and spatial distribution, were studied in two natural water pools at Jalisco, México, from December 1997 through November 1998. Maximum monthly abundance in Agua Dulce lake and El Ermitaño estuary was 86 471 birds (29 686 in Agua Dulce and 56 785 in Ermitaño), with a total cummulative abundance of 179 808 individuals (66 976 in Agua Dulce and 112 832 in Ermitaño). A total of 87 waterbirds species were recorded, 78 in Agua Dulce and 73 in Ermitaño. The higher species richness and abundance was observed during winter, when migratory species arrived. Most species prefered shallow waters, except seabirds which prefered protected areas such as dunes in Agua Dulce. Other groups, like ducks and related species, prefered low salinity areas, for example in the south-east area of Ermitaño. The higher abundance of the shorebirds was found when the water level on the estuary was low. Herons were seen often at areas with high salinity and influenced by tides (e.g. mouth of Ermitaño).